Buckling-Restrained-Lug Connection for Energy Dissipation. Issue 1 (January 2013) - Chan, Ricky W.K.; Albermani, Faris
Under extreme loading conditions such as an earthquake event considerable amount of energy is imparted to a structure. To protect the structure and to minimize damages, a method is to divert a portion of the input energy into designated energy dissipating devices. A new energy dissipation device is presented in this paper. The device is referred to as Buckling-Restrained-Lug (BRL) which can be incorporated in structural joints. The device is composed of a short segment of a steel strut embedded inside a mortar filled jacket which makes the BRL's capacity governed by the squash load under axial tension or compression. The BRL dissipates energy through axial yielding of the steel strut. Analytical, finite element modeling and experimental results of the proposed BRL are presented and compared. Implementation of the BRL in a beam-to-column connection that results in a dissipative partial-moment-resisting joint is proposed. Based on the obtained results, the paper advocates the consideration of the BRL as a viable, compact and low-cost passive energy dissipation device.